Synergic role of platinum (Pt) and molybdenum trioxide (MoO3) promoted HBEA zeolite towards n-heptane isomerization - L. P., Teh; H. D., Setiabudi; S. M., Sidik; N. H. R., Annuar; A. A., Jalil (Elsevier, 2021)
The potentiality of Pt and MoO3 loading on HBEA zeolite in enhancing n-heptane isomerization was investigated. The multiple characterization techniques revealed the engagement of Pt and MoO3 on the lattice or defect structures of the HBEA framework. Furthermore, the occurrence of dealumination was confirmed by the existence of hydrated aluminium-molybdate, Al2-(MoO4)3. These findings proposed the presence of strong metal-support interactions. The n-heptane isomerization was comparatively investigated over Pt and MoO3 modified catalysts, and significantly higher rate of n-heptane conversion (0.059 μmol/g-cat m2 s) and rate of iso-heptane formation (0.026 μmol/g-cat m2 s) were achieved with Pt/MoO3-HBEA catalyst. The catalytic performance followed the order of Pt/MoO3-HBEA > MoO3-HBEA > Pt-HBEA > HBEA. It is anticipated that the results of in-situ FTIR studies of low-temperature hydrogen adsorption and n-heptane adsorption analyses help elucidate the isomerization mechanism and indicated there was a prerequisite for the presence of both Pt and MoO3 as dissociation and adsorption active sites for enhanced n-heptane isomerization. This study sheds light on the design of new type of MoO3 based catalysts for isomerization reaction.